Monetary Policy in Low Income Countries in the Face of the Global Crisis : The Case of Zambia - Benes, Jaromir (IMF Working Papers; Working Paper ;, 2012)
We develop a DSGE model with a banking sector to analyze the impact of the financial crisis on Zambia and the role of the monetary policy response. We view the crisis as a combination of three related shocks: a worsening in the terms of the trade, an increase in the country's risk premium, and a decrease in the risk appetite of local banks. We characterize monetary policy as "stop and go": initially tight, subsequently loose. Simulations of the model broadly match the path of the economy during this period. We find that the initial policy response contributed to the domestic impact of the crisis by further tightening financial conditions. We study the factors driving the "stop" part of policy and derive policy implications for central banks in low-income countries.